Simulation and Examination of a Signal Masking Chaotic Communication System, Based on the Duffing Oscillator - Cherneva, Galina; Dimkina, Elena (Communications - Scientific letters of the University of Zilina, 2013)
The study in this paper is focused on the applications of the chaotic Duffing oscillator to signal masking communication scheme. Using the concept of synchronized chaotic systems the signal masking approach is demonstrated with the Duffing oscillator implemented in both the transmitter and receiver. The chaotic masking signal is added at the transmitter to the information signal, and at the receiver, the masking is regenerated and subtracted from the received signal. Chaotic behavior and chaotic masking scheme are designed and simulated using Simulink/Matlab program. All the results are used to illustrate the effectiveness and the applicability of the Duffing oscillator in signal masking communication.